STRUKTUR KOMUNITAS TANAMAN BAWAH, DAN JENIS-JENIS YANG BERMANFAAT SEBAGAI TANAMAN OBAT DI KAWAASAN HUTAN LINDUNG KALIURANG - SUTOMO, SUTOMO; UNDAHARTA, NI KADEK EROSI; LUGRAYASA, N. LUGRAYASA (Buletin Udayana Mengabdi; Vol 5 No 1 (2006): Volume 5 No.1 – April 2006, 2012)
ABSTRACT Low layer plants as one of component in forest ecosystem today still lack of attention due to the limited information about them. Low layer plants plays an important role in forest ecosystem, and also they are potential to be use as a medicinal plants, genetic resources and other uses that are not yet revealed. For that reason reseach about Low Layer Plants ; Community Structure and Their Use as Medicinal Plants need to be conducted. The objective of this research was to get the information about : (1) Community structure of low layer plants in compartment seven Kaliurang protection forest and (2) Species that are use as a medicinal pants. To fulfill this goal, small plots of 1 x 1 m along forest pathways were made in sampling area. Result showed that as many as 47 species of low layer plants were found in sampling area. There were five main species which has high importance value index : Eupatorium riparium Regel. with importance value index 21,29%, followed by Eleusine indica Gaertn.17,82 % , Oplismenus burmanii Beauv. 14,61 %, Diplazium proliferum 14,04% and Panicum reptans Kunth. 11,27 %. From those 47 species, as many as 10 species are known as a medicinal plants, they are : Melastoma malabathricum L., Physalis angulata Heyne, ex. Wall., Ageratum conyzoides Linn., Elephantopus scaber Linn., Psidium guajava Linn., Justicia gendarussa Linn., Alocasia macrorhiza Schott., Eleusine indica Gaertn., Villebrunea rubescens Bl. and Phyllanthus niruri L.